Model for the analysis of urban mobility using the complex networks formalism (2015)
Urban mobility is a key variable for planning, therefore it is necessary to understand the patterns of mobility and other aspects of the cities for a better decisión-making. It is posible to represent the commuting fluxes of people in the city through networks and, in order to understand the system and support decisión making in urban planning, it is possible to analyze urban mobility from the methodological conceptual and analytical tolos given by complex networks formalism. In This thesis, we constructed complex mobility networks of three Colombian cities from mobility surveys at the scale of urban planning; we identified and analyzed the topological properties of networks in daily and hourly time scales in order to identify peak hour patterns. We analyzed mobility networks by the socioeconomic status of the traveler and we found significant differences in mobility patterns depending on these characteristics. We deepened our analysis through multiplex networks including the transportation mode as layers, which allows us to study patterns of social segregation and the multimodality of urban mobility in a novel and integrated way. Finally, from mobility and segregation patterns found, we created a model to represent and to study the spreading dynamics of infectious diseases in the city, base don the movement and interaction of individuals. Results of the model allowed us to identify the socioeconomic groups more vulnerable to the disease spread.